PROBLEMATIKA PEMBELAJARAN PAI DENGAN MENERAPKAN KURIKULUM MERDEKA - Ayu Fidiasari, Riska; Noorazmah Hidayati; Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Indonesian education system has undergone 11 curriculum changes since independence. SMAN 3 Palangka Raya, a school that has implemented the Merdeka curriculum, has been implementing it. The impact of implementing this curriculum on Islamic religious education subjects is that teachers are not fully familiar with the Merdeka curriculum, which has impacted learning methods. The study used a qualitative and field research approach. The purpose of the study was to describe and analyze the learning process, problems, and efforts to overcome them in implementing the Merdeka Curriculum in Islamic Religious Education (PAI) learning at SMAN 3 Palangka Raya. The study revealed that the Merdeka curriculum has been implemented since the 2021/2022 academic year, with an emphasis on student-centered intracurricular activities through interactive methods such as discussions, presentations, group projects, and direct worship practices. The approach integrates the development of the Pancasila Student Profile through real-world problem-based projects, as well as teacher flexibility in selecting contextual teaching materials tailored to students' backgrounds. Islamic religious education teachers face problems such as low student motivation and learning awareness due to diverse characteristics, high absenteeism, limited infrastructure, increasing administrative burdens, and difficulties in authentic assessment of attitudes and skills. These factors complicate innovative learning strategies that require active student participation. Solutions include intensive outreach and time allocation coordination, teacher training through workshops, gradual infrastructure improvements using BOS funds and local materials, parental involvement through counseling, development of assessment instruments, and student mapping for a differentiated approach. These steps enhance the effectiveness of the Independent Curriculum in a sustainable manner.